Analysis of Customer Satisfaction with The Quality of Online Motorcycle Taxi Services (Maxim) in Tegal City - Ramadhan, Muhammad Rayhan; Brilianti, Dani Fitria (Kirana Publisher (KNPub), 2025)
In this era, people have a variety of different activities. Transportation service providers compete to attract customers by improving service, simplifying the ordering process, price, and timeliness. This study aims to determine the effect of Service Quality and Customer Satisfaction on online motorcycle taxi transportation modes (Case Study on Maxim in Tegal City, Central Java). The research was conducted by distributing questionnaires to respondents as many as 100 students using online motorcycle taxis. The data collection technique used a questionnaire in the form of a google form aimed at users of Maxim online transportation services in Tegal City. Respondents in this study amounted to 100 respondents. The results of this study were to find out that Maxim satisfied the people of Tegal city. Recommendations from me for maxim services are further improved so that people are more satisfied